Improving The Order Fulfilment Process At A Metalwork Company - Dias, José António (2020)
This article describes the 14 measures implemented at a company in the metalwork sector with a view to improving its order fulfilment process. Based on Lean thinking, each of the actions, as well as their potential impact on the process, is explained. Despite the constraints encountered during implementation, and the fact that manufacturing processes are invariably different, the overall results achieved were satisfactory. As a result of the interventions, internal functions were revised and processes simplified. There was also a reduction of 25% in budgeting time, as well as an improvement in communication systems and production management. One additionally was achieved the reorganization of storage spaces, a reduction in logistic operation times of about 20% and a decrease in the time spent accessing tools in near 61%. Far more important than the first results obtained is the company’s current commitment to the pursuance of these measures, allowing the different actions to generate synergies and produce improvements, which will undoubtedly set the company on the course of Lean culture.